Passenger for millenniums: association between stenothermic microcrustacean and suctorian epibiont - the case of Eurytemora lacustris and Tokophyra sp - Łukasz Sługocki (Nature Portfolio, 2020)
Abstract Epibionts often colonize the exoskeleton of crustaceans, which sometimes results in the development of a long-term relationship between them. Our present work confirmed that a specific epibiont is closely associated with the pelagic calanoid copepod Eurytemora lacustris, regardless of the region, which suggests a preserved interaction between these species. Molecular analyses revealed that the epibiont belongs to the genus Tokophrya. We also found that the level of basibiont colonization is related to its size and identified that the most intensely inhabited body parts are those located near the center of the copepod body. We hypothesize that the relationship between Eurytemora (basibiont) and Tokophrya (epibiont) was established during the Quaternary period, following which these two populations were fragmented into lakes where they survived in close interaction. In addition, we suppose that the close relationship between the two species indicates the coevolution of stenotherms. Further studies on the interactions between Eurytemora lacustris and Tokophrya are required in order to gain insight into the long-term relationship between the copepods and the epibionts.